THE RHETORIC FEATURES OF ENGLISH AND INDONESIAN ESSAYS MADE BY EFL UNDERGRADUATE STUDENTS - Teguh Budiharso (TEFLIN, 2006)
This study was aimed at analyzing the similarities and differences between English and Indonesian essays made by EFL undergraduate students. The problems rise from the transfer of first language (L1) cultural conventions to second language (L2) performance. Three rhetorical aspects: general patterns of thought (linear or non-linear), development of ideas, and coherence were compared and analyzed by using content analysis. The results of the analysis showed that EFL students devoted similar rhetoric features in writing English and Indonesian essays. The rhetoric similarity was shared in the use of linearity and non-linearity of ideas, the development of ideas in the whole essays as well as the coherence quality.